Camera girl : the coming of age of Jackie Bouvier Kennedy - Anthony, Carl Sferrazza (Gallery Books, an imprint of Simon & Schuster, Inc., 2023)
"Camera Girl brings to cinematic life Jackie Kennedy's years as a young woman chafing at the expectations of her family and her era as she seeks to follow her dreams of becoming a famous writer. Set primarily during the underexamined years of 1950-1954, when Jackie was 20 to 25 years old, the book recounts the extraordinary story of her late college years, coming-of-age, and her life as a young female journalist. Before she met Jack Kennedy, Jacqueline Bouvier was a columnist at the Washington Times-Herald, the paper's "Inquiring Camera Girl," who posed intelligent and amusing questions to the public on the streets of D.C. (while also snapping their photos with her unwieldy Leica camera). She then fashioned the results into a daily column, 600 of which were published in total. Carl Anthony, author and leading expert on First Ladies, uses these columns and other writings of hers from that time, as well as a trove of revealing interviews he has conducted with her friends and colleagues, to offer a fresh and modern perspective on the young woman who would later become one of the world's most beloved icons. It's a glamorous, surprising, and distinctly feminist story about a woman determining her own priorities and defining herself, told with admiration and empathy, as well as journalistic rigor and historical accuracy"--